Perancangan Sistem Informasi Penerimaan Siswa Baru di SMK Harapan Bangsa Berbasis Web Menggunakan CodeIgniter 4 - Da Costa, Nova Selajar; Karo-Karo, Panser; Faizah, NM (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
The admission of new students is a critical process in educational institutions, designed to select candidates based on specific criteria set by the school. This process typically involves multiple stages, including registration, selection through testing, and the announcement of results. However, at SMK Harapan Bangsa, this process has been managed manually using paper-based documentation and Microsoft Excel, which is inefficient and prone to errors. This study aims to develop a web-based information system for new student admissions using the CodeIgniter 4 framework and MySQL database to streamline and enhance the process. The software development methodology employed in this research is the Waterfall model, which consists of analysis, design, implementation, and system testing stages. The result of this research is an information system that simplifies the access to new student admission information for parents and students, enabling them to register online and monitor the selection results more efficiently. Additionally, the system supports the school in automatically archiving and organizing registration data. This web-based solution offers a more structured and error-free process, significantly improving the overall efficiency and accuracy of the admissions procedure.